Two-dimensional-three-dimensional registration for fusion imaging is noninferior to three-dimensional- three-dimensional registration in infrarenal endovascular aneurysm repair - Schulz, Christof; Böckler, Dittmar; Krisam, Johannes; Geisbüsch, Philipp (Journal of vascular surgery, 2019)
Background - Fusion imaging is a tool for intraoperative three-dimensional (3D) guidance in endovascular aneurysm repair (EVAR). In many aortic centers, the registration for location is based on an intraoperative 3D dataset acquired by means of cone-beam computed tomography (3D-3D registration). Another registration method is based on two two-dimensional (2D) images (lateral and posteroanterior) acquired with the use of intraoperative fluoroscopy for registration with a computed tomographic angiogram (2D-3D registration). The aim of the present study was to compare 2D-3D registration with 3D-3D registration regarding noninferiority in accuracy and to describe radiation exposure and ease of use of both modalities. - Methods - From December 2014 to September 2015, 50 sequentially enrolled patients received EVAR with the use of fusion imaging using 2D-3D registration. No adjustments were made until the first angiography with inserted stent graft. The deviation of fusion imaging to the actual position of the lower renal artery compared with digital subtraction angiography was measured. A historic cohort of 101 patients treated with EVAR and fusion imaging with 3D-3D registration (3D-3D cohort) served as the control group for this study. - Results - Craniocaudal deviation did not differ significantly (4.6 ± 4.4 mm in the 2D-3D cohort vs 3.6 ± 3.9 mm in the 3D-3D cohort; P = .17). The difference of the means was 1.05 mm with a 95% confidence interval of −2.45 to 0.34 and a P value for the noninferiority test of .0249, indicating that 2D-3D registration was noninferior in terms of a margin of δ = 2.5 mm. 2D-3D registration was significantly faster with significantly less additional radiation necessary: 0.45 ± 0.28 vs 45.7 ± 9.1 Gy·cm2 in the 3D-3D cohort (P < .001); 2.3 ± 1.3 vs 5.3 ± 4.3 minutes in the 3D-3D cohort (P < .001). - Conclusions - Fusion imaging during EVAR with the use of 2D-3D registration is feasible in routine EVAR. Our findings of two consecutive cohorts with the same clinical, hardware, and software setup used for the procedures underscore that the accuracy of 2D-3D registration is noninferior to that of a 3D-3D registration workflow, with advantages in terms of radiation exposure, intraoperative time demand, and ease of use.